Methylotrophic methanogens everywhere — physiology and ecology of novel players in global methane cycling. (10th December 2019) - Söllinger, Andrea; Urich, Tim
Abstract : Research on methanogenic Archaea has experienced a revival, with many novel lineages of methanogens recently being found through cultivation and suggested via metagenomics approaches, respectively. Most of these lineages comprise Archaea (potentially) capable of methanogenesis from methylated compounds, a pathway that had previously received comparably little attention. In this review, we provide an overview of these new lineages with a focus on the Methanomassiliicoccales . These lack the Wood–Ljungdahl pathway and employ a hydrogen-dependent methylotrophic methanogenesis pathway fundamentally different from traditional methylotrophic methanogens. Several archaeal candidate lineages identified through metagenomics, such as the Ca . Verstraetearchaeota and Ca . Methanofastidiosa, encode genes for a methylotrophic methanogenesis pathway similar to the Methanomassiliicoccales . Thus, the latter are emerging as a model system for physiological, biochemical and ecological studies of hydrogen-dependent methylotrophic methanogens. Methanomassiliicoccales occur in a large variety of anoxic habitats including wetlands and animal intestinal tracts, i.e. in the major natural and anthropogenic sources of methane emissions, respectively. Especially in ruminant animals, they likely are among the major methane producers. Taken together, (hydrogen-dependent) methylotrophic methanogens are much more diverse and widespread than previously thought. Considering the role of methane as potent greenhouse gas, resolving the methanogenic nature of a broad range of putative novel methylotrophic methanogens and assessing their role in methane emitting environments are pressing issues for future research on methanogens.